The Strategies of Pesantren Administrators in Addressing Students' Delinquent Behaviour at Assalam Al-Islami Islamic Boarding School, Sungai Lilin, Musi Banyuasin - Abdullah Nizam, Ali Musa Lubis (Lembaga Bale Literasi, 2025)
This study examined the forms, contributing factors, and administrators' strategies for addressing student misconduct at Pondok Pesantren Assalam Al-Islami, Sungai Lilin, Musi Banyuasin, focusing on smoking and absence from congregational prayer. Using a qualitative case study design, data were collected through in-depth interviews, field observation, and a four-month institutional violation log, then analysed using the interactive model of data condensation, display, and conclusion verification, with credibility established through triangulation. Findings showed 47 documented violations among 37 santri, comprising prayer absenteeism (70.2 %) and smoking (29.8 %), shaped by internal factors, peer influence, family habits, and supervisory gaps within the pesantren. Administrators responded through a structured cycle of planning, organizing, directing, controlling, and evaluation, combining preventive supervision, a staged warning system, parental involvement, and educative-restorative sanctions rather than punishment alone. The system, however, remained constrained by limited personnel. These findings indicate that effective management of student misconduct in pesantren settings requires aligning disciplinary strategy with adequate supervisory capacity.